Product of infinite sums

Algebra Level 3

Let S a = x = 0 1 a x . S_a=\displaystyle \sum_{x=0}^{\infty}\frac{1}{a^x}.

If i = 2 2013 S i = λ \displaystyle\prod_{i=2}^{2013}S_i= \lambda
, what is the value of λ 2013 = ? \frac{\lambda }{2013}=?


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

By the formula of sum of infinite geometric series, we have

S a = 1 + 1 a + 1 a 2 + 1 a 3 + S a = 1 1 1 a S a = a a 1 S_a = 1 + \frac{1}{a} + \frac{1}{a^2} + \frac{1}{a^3} + \cdots \Rightarrow S_a = \frac{1}{1-\frac{1}{a}} \Rightarrow S_a = \frac{a}{a-1} .

Checking λ \lambda , we see that the product telescopes:

λ = 2 × 3 2 × × 2012 2011 × 2013 2012 λ = 2013 \lambda = 2 \times \frac{3}{2} \times \cdots \times \frac{2012}{2011} \times \frac{2013}{2012} \Rightarrow \lambda = 2013 .

Therefore, ? = 1. \ \boxed{? = 1.}

Great solution, as always.

Bogdan Simeonov - 7 years, 5 months ago

Log in to reply

It's the same as yours :P

Guilherme Dela Corte - 7 years, 5 months ago

Log in to reply

That's why it's great :D

Bogdan Simeonov - 7 years, 5 months ago
Bogdan Simeonov
Dec 28, 2013

We know that S a = a a 1 S_a=\frac{a}{a-1} . That means that 2 2013 S i = 2 1 3 2 4 3 . . . 2012 2011 2013 2012 = 2013 = λ \prod_{2}^{2013}S_i=\frac{2}{1}\frac{3}{2}\frac{4}{3}...\frac{2012}{2011}\frac{2013}{2012}= 2013=\lambda .So λ 2013 = 1 \frac{\lambda}{2013}=\boxed1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...